2019
DOI: 10.1002/lt.25345
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Tumor From Bland Portal Vein Thrombus in Liver Transplant Candidates With Hepatocellular Carcinoma: the A‐VENA Criteria

Abstract: Differentiating tumor versus bland portal vein thrombosis (PVT) is essential in determining liver transplantation (LT) candidacy for patients with hepatocellular carcinoma (HCC). We aimed to evaluate radiographic and clinical features that could noninvasively distinguish tumor PVT from bland PVT in HCC patients. Of 467 patients with HCC listed for LT from 2004 to 2011, 59 (12.6%) had PVT and 12 of 59 (20.3%) were deemed malignant. When comparing tumor versus bland PVT, thrombus enhancement was seen in 100% ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 27 publications
1
48
1
1
Order By: Relevance
“…In an effort to improve the quality of the study, a centralized radiological assessment confirmed the presence of a vascular invasion in 30 patients, who were the final studied population. This assessment was based on previously defined characteristics known to be associated with a vascular invasion, including thrombus enhancement, venous expansion, neovascularity, and proximity of the thrombus with a previously treated HCC nodule .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to improve the quality of the study, a centralized radiological assessment confirmed the presence of a vascular invasion in 30 patients, who were the final studied population. This assessment was based on previously defined characteristics known to be associated with a vascular invasion, including thrombus enhancement, venous expansion, neovascularity, and proximity of the thrombus with a previously treated HCC nodule .…”
Section: Discussionmentioning
confidence: 99%
“…It could affect either the portal vein or hepatic veins, and was defined as the presence of a contrast‐enhancing endovascular mass located in the area of a known HCC. The lesion could also demonstrate A‐VENA criteria, including a venous expansion, and/or intra‐thrombus neovascularity and/or direct invasion of the portal vein/hepatic vein . In order to improve the homogeneity of the radiological diagnosis, imaging was centrally assessed by an expert liver radiologist to confirm the presence of macrovascular invasion.…”
Section: Methodsmentioning
confidence: 99%
“…65 Making the diagnosis of tumor thrombus generally requires close correlation with a patient's clinical history, serological studies, and cross-sectional imaging characteristics, though diagnostic criteria have recently been proposed in a single-center retrospective study. 65,66 Many patients with cirrhosis who develop a PVT are asymptomatic due to splanchnic decompression through an existing spontaneous portosystemic shunt, and the PVT is discovered incidentally detected on routine US screening for HCC. 1 Some patients may also present with symptoms of abdominal discomfort or in the setting of hepatic decompensation, such as new or worsening ascites or gastrointestinal bleeding.…”
Section: Diagnosis and Natural Historymentioning
confidence: 99%
“…(2) In this issue of Liver Transplantation, Sherman et al describe a set of criteria for noninvasive diagnosis of PVTT. (3) Their criteria, dubbed the A-VENA score, consist of 4 imaging features and 1 laboratory marker associated with PVTT. Imaging markers included thrombus enhancement, venous expansion, neovascularity, and proximity to tumor or prior treatment site.…”
Section: See Article On Page 207mentioning
confidence: 99%
“…In this issue of Liver Transplantation , Sherman et al describe a set of criteria for noninvasive diagnosis of PVTT . Their criteria, dubbed the A‐VENA score, consist of 4 imaging features and 1 laboratory marker associated with PVTT.…”
mentioning
confidence: 99%